Germination of Erysimum pieninicum and Erysimum odoratum seeds after various storage conditions - Csontos, Péter; Rucinska, Anna; Puchalski , Jerzy T. (JOURNAL OF LANDSCAPE ECOLOGY, 2010)
Erysimum pieninicum and E. odoratum have similar morphology and habitat preference, however biogeography of the two species is contrasting. E. pieninicum is a narrow endemic, expressing a very limited distribution in SE Poland, whereas E. odoratum is rather frequent in Hungary and the surrounding countries. The aim of this paper is to investigate the germination behaviour of the two species and to highlight if the differences in the germination of the two species could be related with their distribution patterns.Prior to germination tests, seeds of the two species were subjected to three different storage conditions:1) room temperature (RT); 2) room temperature followed by 40 days at +4 °C before germination test (CT); 3) eight years storage in liquid nitrogen (LN) (for E. pieninicum only). After surface sterilisation of the seeds germination tests in Petri-dishes were initiated on 5th March 2009, and were terminated after 25 days.The studied Erysimum species germinated very fast showing a germination pattern of “Erysimum wittmannii type” sensu Czarnecka  and Władyka  (2007). E. odoratum expressed a relatively low rate of total germination percentage (around 20%) that does not correspond previous reports. The very high germination rate of E. pieninicum (around 97% and 99%) found in RT and CT treatments, respectively, agrees with results of Czarnecka and Władyka. Cold treatment did not influence germination of the studied Erysimum species. In case of the LN treatment E. pieninicum retained a high rate of germination (81.65%).Considering the results of the present study and also the published results of other researchers, germination behaviour of E. pieninicum does not seem to be a limiting factor for the distribution of this species. According to their seed biological characteristics (preserved viability in seed gene banks for long time and sudden germination without the need of dormancy breaking treatments) E. pieninicum and E. odoratum are promising candidates for nature conservation and habitat restoration projects.
Keywords: cold treatment; germination; liquid nitrogen; seed storage; protected species; endemic species; wallflower